Photosensitive resin composition and cured film, and color filter, solid-state imaging device, and fingerprint authentication device using the cured film

The photosensitive resin composition, featuring a siloxane resin and metal chelating agents, addresses the issues of film stress and adhesion in optical under-display fingerprint authentication devices, resulting in a cured film with enhanced transparency, chemical resistance, and substrate stability.

JP7670241B1Active Publication Date: 2025-04-30TORAY INDUSTRIES INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024537900
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2024-06-18
Publication Date
2025-04-30
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

Existing photosensitive resin compositions for optical under-display fingerprint authentication devices face challenges with high film stress, warping of substrates, and low adhesion to metal layers containing molybdenum, aluminum, or nickel, especially when forming thick films.

Method used

A photosensitive resin composition comprising a siloxane resin with radically polymerizable groups, a metal chelating agent such as an aluminum or zirconium chelate compound, and a photoradical polymerization initiator, which together provide high transparency, chemical resistance, low film stress, and excellent adhesion to metal layers.

Benefits of technology

The composition achieves a cured film with high transparency and chemical resistance, low film stress, and strong adhesion to metal layers, even in thick films, thereby reducing substrate warping and improving the reliability of optical under-display fingerprint authentication devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670241000001
    Figure 0007670241000001
  • Figure 0007670241000002
    Figure 0007670241000002
  • Figure 0007670241000003
    Figure 0007670241000003
Patent Text Reader

Abstract

The present invention has an object to provide a photosensitive resin composition which, when formed into a cured film, has high transparency and chemical resistance, low film stress, and high adhesion to a metal layer containing molybdenum, aluminum, or nickel. In order to solve the above object, the present invention provides a photosensitive resin composition comprising a siloxane resin having a radical polymerizable group, a metal chelating agent, and a photoradical polymerization initiator, wherein in the siloxane resin having a radical polymerizable group, (R) 2 SiO 2 / 2 The present invention proposes a photosensitive resin composition in which the content of organosilane units (D units) represented by (R is an organic group) is 30 mol % or more and 85 mol % or less relative to 100 mol % of all organosilane units.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photosensitive resin composition, a cured film, and a color filter, a solid-state imaging device, and a fingerprint authentication device each including the photosensitive resin composition and a cured film. [Background technology]

[0002] In recent years, mobile display devices such as smartphones and tablet PCs (personal computers) are equipped with biometric authentication functions for unlocking and identity authentication. Among biometric authentication methods, fingerprint authentication in particular is inexpensive, compact, and highly convenient, and is therefore currently installed in many devices.

[0003] Conventionally, fingerprint authentication has generally been performed by mounting a capacitive fingerprint authentication device on the bezel of a display (around the display). However, the trend for smartphones is toward full-screen displays, and the bezel is being eliminated. This has created a need for fingerprint authentication devices to be mounted under the display, in a so-called "under-display" configuration.

[0004] The main authentication methods being considered for under-display fingerprint authentication devices are ultrasonic and optical. The ultrasonic method is characterized by high authentication accuracy and fast authentication speed, but its adoption rate is still low and manufacturing costs remain high. On the other hand, the optical method is currently the mainstream method due to its versatility, which allows it to be introduced not only to organic light-emitting diode displays but also to liquid crystal displays, and its manufacturing costs are on the decline.

[0005] Generally, optical fingerprint authentication devices have the problem of having lower authentication accuracy than ultrasonic types, but a thin optical under-display fingerprint authentication device that can be installed in the very narrow space between the battery and the screen has been proposed as an optical fingerprint authentication device with high authentication accuracy (see, for example, Patent Document 1 and Patent Document 2).

[0006] The optical under-display type fingerprint authentication device described in Patent Document 2 is composed of a substrate, a sensor, a light-shielding layer, a transparent medium layer, and a microlens. Methods for forming the transparent medium layer include a method of forming it by screen printing and a method of forming it by a photolithography method using a photosensitive material, but the latter method, which excels in positional accuracy and dimensional accuracy that are important for improving authentication accuracy, has attracted attention.

[0007] Also, a photosensitive resin composition containing a specific alkali-soluble silicone resin or the like has been proposed as a photosensitive material capable of forming a thick film and excellent in heat resistance, transparency, crack resistance, and thermal shock test resistance (see, for example, Patent Document 3). Also, a photosensitive resin composition containing polysiloxane, a photosensitizer, a polymerizable compound having a phosphorus atom, and a silane compound having a ureido group has been proposed as a photosensitive material having excellent adhesion to glass substrates and metal substrates and excellent chemical resistance (see, for example, Patent Document 4). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2020-35327 A [Patent Document 2] International Publication No. 2020 / 038408 [Patent Document 3] International Publication No. 2013 / 031985 [Patent Document 4] International Publication No. 2019 / 102655 Summary of the Invention [Problem to be solved by the invention]

[0009] The diameter of the microlens applied to the fingerprint authentication device is generally larger than that of the microlens applied to the CMOS image sensor, and therefore the focal length, which is the distance from the center point of the microlens to the image sensor, is longer. Therefore, the transparent medium layer formed between the microlens and the image sensor needs to have a thickness of about 10 μm to 200 μm, and when forming such a thick film, the film stress becomes important. The film stress is the mechanical stress that occurs when a cured film is formed on a flat substrate, for example, the contraction stress accumulated inside the film. If the film stress is large, the warping of the substrate becomes large during the film formation, and problems such as errors occur during the substrate transportation occur. Therefore, a material with low film stress when it is formed into a cured film to suppress the warping of the substrate is required.

[0010] In addition, since the production lines for manufacturing fingerprint authentication devices often utilize the production lines for TFTs (thin film transistors), metal layers containing molybdenum, aluminum, or nickel are generally used as the light-shielding layers and sensor lead wires in fingerprint authentication devices. Therefore, the material for forming the transparent medium layer must be resistant to the chemicals used when laminating these metal layers on top, and must also have excellent adhesion to these metal layers.

[0011] That is, the material forming the transparent medium layer of the optical under-display type fingerprint authentication device must have high transparency and chemical resistance, low film stress, and high adhesion to the metal layer containing molybdenum, aluminum, or nickel. Furthermore, there are cases where it is required to be able to form a pattern of a thick film with a thickness of 10 μm or more.

[0012] On the other hand, as mentioned above, for example, Patent Documents 3 and 4 propose various materials, but the material described in Patent Document 3 has low adhesion to metal layers containing molybdenum, aluminum, or nickel, and in thick films exceeding 10 μm used in fingerprint authentication devices, the film stress of the cured film is large, which causes warping of the substrate.

[0013] Furthermore, the material described in Patent Document 4 has a similar problem in that, in a thick film exceeding 10 μm, the film stress of the cured film is large, causing warping of the substrate.

[0014] The present invention has been made in view of the problems of the conventional technology, and an object of the present invention is to provide a photosensitive resin composition which, when formed into a cured film, has high transparency and chemical resistance, low film stress, and high adhesion to a metal layer containing molybdenum, aluminum, or nickel. [Means for solving the problem]

[0015] The object of the present invention is achieved by the following configuration.

[0016] A photosensitive resin composition comprising the following components (a) to (c), wherein in component (a), (R)SiO 2 / 2 A photosensitive resin composition containing 30 mol % or more and 85 mol % or less of organosilane units represented by (R is an organic group) (such organosilane units will be referred to as "D units" hereinafter) relative to 100 mol % of all organosilane units. Component (a): Siloxane resin having a radical polymerizable group (b) Component: Metal chelating agent Component (c): Photoradical polymerization initiator.

[0017] Moreover, more preferred aspects of the present invention are, for example, as follows. The photosensitive resin composition described above, wherein either or both of an aluminum chelate compound and a zirconium chelate compound are used as the component (b). The photosensitive resin composition, wherein the content of the component (b) is 0.1% by weight or more and 5% by weight or less, based on 100% by weight of the solid content of the photosensitive resin composition. The photosensitive resin composition wherein the component (b) is either or both of an aluminum chelate compound and a zirconium chelate compound, the content of the component (b) is from 0.1 to 5% by weight, based on 100% by weight of the solid content of the photosensitive resin composition, and further wherein, in the D units, R is a phenyl group, and the content of the D units is from 30 to 65 mol%, based on 100 mol% of all organosilane units. the photosensitive resin composition in which the component (b) is either or both of an aluminum chelate compound and a zirconium chelate compound, the content of the component (b) is from 0.1 to 5% by weight, based on 100% by weight of the solid content of the photosensitive resin composition, and further in which R in the D units is a phenyl group and the content of the D units is from 30 to 65 mol%, based on 100 mol% of all organosilane units, and the component (a) contains either or both of a carboxyl group and a dicarboxylic anhydride group. The photosensitive resin composition further comprises the following component (d): (d) Component: Monofunctional (meth)acrylate Effect of the Invention

[0018] According to the photosensitive resin composition of the present invention, it is possible to provide a photosensitive resin composition which, when cured, has high transparency and chemical resistance, low film stress, and high adhesion to a metal layer containing molybdenum, aluminum, or nickel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be described in more detail below. Preferred embodiments of the photosensitive resin composition, cured film, color filter, solid-state imaging device, and fingerprint authentication device of the present invention will be specifically described below, but the present invention is not limited to the following embodiments and can be modified in various ways depending on the purpose and application.

[0020] The photosensitive resin composition of the present invention contains the following components (a) to (c): Component (a): a siloxane resin having a radically polymerizable group. (b) Metal chelating agents. (c) Photoradical polymerization initiator.

[0021] In the component (a), (R)2SiO 2 / 2 The content of organosilane units (D units) represented by (R is an organic group) is 30 mol % or more and 85 mol % or less with respect to 100 mol % of all organosilane units.

[0022] The siloxane resin used as component (a) in the photosensitive resin composition of the present invention refers to a polymer having a siloxane skeleton (-Si-O- bond) as a repeating unit. In the present invention, the organosilane unit refers to a silane unit having at least one organic group on the side chain of the siloxane skeleton. In addition, R contained in the D unit is an organic group, and such an organic group refers to a group having a carbon atom bonded to a silicon atom of the siloxane skeleton, and specific examples thereof are as described below.

[0023] The inclusion of component (a) makes it possible to form a cured film that is highly transparent and has excellent heat resistance and weather resistance, which is due to the fact that component (a) has a siloxane skeleton in its main chain.

[0024] The weight average molecular weight (Mw) of component (a) is preferably 500 or more, more preferably 1,000 or more, from the viewpoint of further improving chemical resistance. On the other hand, the weight average molecular weight of component (a) is preferably 10,000 or less, more preferably 5,000 or less, from the viewpoint of improving solubility in a developer during pattern formation. Here, the weight average molecular weight of component (a) refers to a polystyrene-equivalent value measured by gel permeation chromatography (GPC).

[0025] The (a) component contains 30 mol % or more and 85 mol % or less of D units relative to 100 mol % of all organosilane units. When the content of D units is 30 mol % or more relative to 100 mol % of all organosilane units, three-dimensional crosslinking can be appropriately suppressed, and a cured film with low film stress and excellent crack resistance can be formed. The content of D units is more preferably 35 mol % or more, and even more preferably 40 mol % or more, relative to 100 mol % of all organosilane units. In addition, when the content of D units is 85 mol % or less relative to 100 mol % of all organosilane units, the crosslink density of the film can be increased, and it is possible to maintain excellent moist heat resistance and sufficient chemical resistance against acids and alkalis. The content of D units is more preferably 75 mol % or less, and even more preferably 65 mol % or less, relative to 100 mol % of all organosilane units. The D units contained in the (a) component may be one type or multiple types.

[0026] In the (a) component, the two Rs in the D unit each preferably independently contain a functional group selected from the group consisting of a methyl group, a phenyl group, a cyclopentyl group, and a cyclohexyl group. However, the two Rs do not simultaneously become methyl groups. In addition, it is preferable that the two Rs each independently are a functional group selected from the group consisting of a methyl group, a phenyl group, a cyclopentyl group, and a cyclohexyl group (however, the two Rs do not simultaneously become methyl groups). By using the (a) component containing such a D unit, three-dimensional crosslinking can be appropriately suppressed due to steric hindrance between the functional groups, and a cured film having low film stress and excellent crack resistance can be formed. The proportion of such D units is preferably 65 mol% or more and 92% mol or less, assuming that the total D units are 100 mol%. From the viewpoint of forming a cured film having low film stress and excellent crack resistance, it is preferable to have a D unit in which both of the Rs are phenyl groups. From the same viewpoint, it is preferable that the D unit in which both R are phenyl groups is contained in an amount of 30 mol % to 65 mol % based on 100 mol % of all organosilane units. Note that, in addition to the D unit as the preferred embodiment described above, the (a) component used in the present invention may contain other organosilane units, such as organosilane units derived from an organosilane compound having a radical polymerizable group, which will be described later.

[0027] The D units contained in the component (a) can be obtained by hydrolysis and condensation of a bifunctional organosilane compound.

[0028] Examples of such bifunctional organosilane compounds include dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, di-n-propyldimethoxysilane, di-n-propyldiethoxysilane, diisopropyldimethoxysilane, diisopropyldiethoxysilane, di-n-butyldimethoxysilane, di-n-butyldiethoxysilane, di-t-butyldimethoxysilane, di-t-butyldiethoxysilane, di-n-pentyldimethoxysilane, di-n-pentyldiethoxysilane, dicyclopentyldimethoxysilane, and Silane, dicyclopentyldiethoxysilane, di-n-hexyldimethoxysilane, di-n-hexyldiethoxysilane, dicyclohexyldimethoxysilane, dicyclohexyldiethoxysilane, diheptyldimethoxysilane, diheptyldiethoxysilane, dioctyldimethoxysilane, dioctyldiethoxysilane, dinonyldimethoxysilane, dinonyldiethoxysilane, didecyldimethoxysilane, didecyldiethoxysilane, ethylmethyldimethoxysilane, ethylmethyldiethoxysilane, n-propylmethyldimethoxysilane, n-propyl pylmethyldiethoxysilane, isopropylmethyldimethoxysilane, isopropylmethyldiethoxysilane, n-butylmethyldimethoxysilane, n-butylmethyldiethoxysilane, t-butylmethyldimethoxysilane, t-butylmethyldiethoxysilane, n-pentylmethyldimethoxysilane, n-pentylmethyldiethoxysilane, cyclopentylmethyldimethoxysilane, cyclopentylmethyldiethoxysilane, n-hexylmethyldimethoxysilane, n-hexylmethyldiethoxysilane, cyclohexylmethyldimethoxysilane, Cyclohexyl methyl diethoxy silane, heptyl methyl dimethoxy silane, heptyl methyl diethoxy silane, octyl methyl dimethoxy silane, octyl methyl diethoxy silane, nonyl methyl dimethoxy silane, nonyl methyl diethoxy silane, decyl methyl dimethoxy silane, decyl methyl diethoxy silane, diphenyl silane diol, diphenyl dimethoxy silane, diphenyl diethoxy silane, methyl phenyl dimethoxy silane, methyl phenyl diethoxy silane, naphthyl methyl dimethoxy silane, naphthyl methyl diethoxy silane,Examples of the silane include biphenylmethyldimethoxysilane, biphenylmethyldiethoxysilane, cyclopentylphenyldimethoxysilane, cyclopentylphenyldiethoxysilane, cyclopentylcyclohexyldimethoxysilane, cyclopentylcyclohexyldiethoxysilane, cyclohexylphenyldimethoxysilane, and cyclohexylphenyldiethoxysilane. Two or more of these may be used.

[0029] Among these, from the viewpoint of being able to form a cured film having excellent resistance to moist heat and chemicals, as well as low film stress and excellent crack resistance, dicyclopentyldimethoxysilane, dicyclopentyldiethoxysilane, dicyclohexyldimethoxysilane, dicyclohexyldiethoxysilane, cyclopentylmethyldimethoxysilane, cyclopentylmethyldiethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylmethyldiethoxysilane, diphenylsilanediol, diphenyldimethoxysilane, diphenyl Preferred are cyclopentylphenyldiethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, cyclopentylphenyldimethoxysilane, cyclopentylphenyldiethoxysilane, cyclopentylcyclohexyldimethoxysilane, cyclopentylcyclohexyldiethoxysilane, cyclohexylphenyldimethoxysilane, and cyclohexylphenyldiethoxysilane, and more preferably selected from diphenylsilanediol, diphenyldimethoxysilane, and diphenyldiethoxysilane.

[0030] The component (a) used in the present invention has a radical polymerizable group. The radical polymerizable group refers to a functional group having a double bond that reacts with a radical generated from a radical polymerization initiator. Examples of the radical polymerizable group include a vinyl group, an allyl group, a methacryl group, an acrylic group, and a styryl group. From the viewpoint of high radical reactivity and further improving the chemical resistance of the cured film and the sensitivity during pattern processing, a methacryl group, an acrylic group, and a styryl group are preferred.

[0031] A simple method for introducing a radically polymerizable group into component (a) is to use an organosilane compound having a radically polymerizable group and subject it to hydrolysis and condensation.

[0032] Examples of organosilane compounds having a radical polymerizable group include vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, allylmethyldimethoxysilane, allylmethyldiethoxysilane, styryltrimethoxysilane, styryltriethoxysilane, styrylmethyldimethoxysilane, styrylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, Silane, 3-acryloxypropyl methyl dimethoxysilane, 3-acryloxypropyl methyl diethoxysilane, 3-methacryloxymethyl trimethoxysilane, 3-methacryloxymethyl triethoxysilane, 3-methacryloxymethyl methyl dimethoxysilane, 3-methacryloxymethyl methyl diethoxysilane, 3-acryloxymethyl methyl dimethoxysilane, 3-acryloxymethyl methyl diethoxysilane, 3-methacryloxyoctyl trimethoxysilane, 3-methacryloxyoctyl triethoxysilane, 3-methacryloxyoctyl methyl dimethoxysilane, 3-methacryloxyoctyl methyl diethoxysilane, 3-acryloxyoctyl methyl dimethoxysilane, 3-acryloxyoctyl methyl diethoxysilane, 3-acryloxyoctyl methyl dimethoxysilane, 3-acryloxyoctyl methyl diethoxysilane. Two or more of these may be used.

[0033] Among these, from the viewpoint of further improving the chemical resistance of the cured film and the sensitivity during pattern processing, styryltrimethoxysilane, styryltriethoxysilane, styrylmethyldimethoxysilane, styrylmethyldiethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-acryloxypropylmethyldiethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-acryloxypropylmethyldiethoxysilane, Preferred are 3-methacryloxymethyltrimethoxysilane, 3-methacryloxymethyltriethoxysilane, 3-methacryloxymethylmethyldimethoxysilane, 3-methacryloxymethylmethyldiethoxysilane, 3-acryloxymethylmethyldimethoxysilane, 3-acryloxymethylmethyldiethoxysilane, 3-methacryloxyoctyltrimethoxysilane, 3-methacryloxyoctyltriethoxysilane, 3-methacryloxyoctylmethyldimethoxysilane, 3-methacryloxyoctylmethyldiethoxysilane, 3-acryloxyoctylmethyldimethoxysilane, and 3-acryloxyoctylmethyldiethoxysilane.

[0034] Among these, from the viewpoint of forming a cured film having excellent wet heat resistance and chemical resistance, low film stress and excellent crack resistance, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-acryloxypropylmethyldiethoxysilane, 3-methacryloxyoctylmethyldimethoxysilane, 3-methacryloxyoctylmethyldiethoxysilane, 3-acryloxyoctylmethyldimethoxysilane, 3-acryloxyoctylmethyldiethoxysilane, more preferred, and bifunctional organosilane compounds such as 3-methacryloxypropylmethyldimethoxysilane and 3-acryloxypropylmethyldimethoxysilane are even more preferred.In addition, to avoid any doubt, the structural unit derived from these bifunctional organosilane compounds having radical polymerizable groups corresponds to D unit.

[0035] When the total organosilane units are taken as 100 mol%, the component (a) preferably contains 5 mol% or more and 50 mol% or less of organosilane units having a radical polymerizable group. When the component (a) contains 5 mol% or more of organosilane units having a radical polymerizable group relative to 100 mol% of the total organosilane units, the crosslink density of the cured film can be increased, and the moisture and heat resistance and chemical resistance can be improved. The ratio of the organosilane units having a radical polymerizable group is more preferably 7 mol% or more, and even more preferably 10 mol% or more, relative to 100 mol% of the total organosilane units. In addition, when the component (a) contains 50 mol% or less of organosilane units having a radical polymerizable group relative to 100 mol% of the total organosilane units, excessive radical reaction can be suppressed, residues during development can be suppressed, and stress on the cured film can be further reduced. The proportion of organosilane units having a radical polymerizable group is more preferably 30 mol % or less, and even more preferably 12 mol % or less, relative to 100 mol % of all organosilane units.

[0036] The component (a) used in the present invention preferably contains either or both of a carboxyl group and a dicarboxylic anhydride group. By containing a carboxyl group or a dicarboxylic anhydride group in its molecular structure, the component (a) suppresses residues during development, improves resolution, and enables the formation of a pattern with excellent resolution even in a thick film with a thickness of 10 μm or more, while improving adhesion to the underlying substrate, metal layer, and resin layer. Examples of the carboxyl group and dicarboxylic anhydride group include an alkylene carboxyl group, a succinic acid group, a succinic anhydride group, a phthalic acid group, and a phthalic anhydride group.

[0037] The component (a) having a carboxyl group or a dicarboxylic anhydride group can be obtained by hydrolysis and condensation of an organosilane compound having a carboxyl group or a dicarboxylic anhydride group.

[0038] Examples of organosilane compounds having a carboxyl group or a dicarboxylic anhydride group include 3-trimethoxysilylpropyl succinic anhydride, 3-triethoxysilylpropyl succinic anhydride, 3-triphenoxysilylpropyl succinic anhydride, 3-trimethoxysilylpropyl cyclohexyl dicarboxylic anhydride, and 3-trimethoxysilylpropyl phthalic anhydride. Two or more of these may be used. Among these, 3-trimethoxysilylpropyl succinic anhydride and 3-triethoxysilylpropyl succinic anhydride are preferred from the viewpoint of suppressing residues during development, improving resolution, and forming a pattern with excellent resolution even in a thick film with a film thickness of 10 μm or more.

[0039] The (a) component preferably contains 1 mol % or more and 30 mol % or less of organosilane units having a carboxyl group or a dicarboxylic anhydride group, when the total organosilane units are taken as 100 mol %. By making the ratio of the organosilane units having a carboxyl group or a dicarboxylic anhydride group 1 mol % or more relative to 100 mol % of the total organosilane units, residues during development are suppressed, resolution is improved, and a pattern with excellent resolution can be formed even in a thick film with a thickness of 10 μm or more. The ratio of the organosilane units having a carboxyl group or a dicarboxylic anhydride group is more preferably 3 mol % or more, and even more preferably 5 mol % or more, relative to 100 mol % of the total organosilane units. In addition, by making the ratio of the organosilane units having a carboxyl group or a dicarboxylic anhydride group 30 mol % or less relative to 100 mol % of the total organosilane units, film loss during development can be suppressed and patterning properties can be improved. The proportion of organosilane units having a carboxyl group or a dicarboxylic anhydride group is more preferably 25 mol % or less, and even more preferably 20 mol % or less, relative to 100 mol % of all organosilane units.

[0040] The component (a) is preferably a hydrolysis condensation product of a bifunctional organosilane compound that provides D units, an organosilane compound having the radically polymerizable group, and an organosilane compound having either or both of a carboxyl group and a dicarboxylic anhydride group, and may further be a hydrolysis condensation product of any of these organosilane compounds with other organosilane compounds.

[0041] Other organosilane compounds include, for example, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, hexyltrimethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-(N,N-diglycidyl)aminopropyltrimethoxysilane, 3-glycidoxy ... Silane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 2-cyanoethyltriethoxysilane, glycidoxymethyltrimethoxysilane, glycidoxymethyltriethoxysilane, 1-glycidoxyethyltrimethoxysilane, 1-glycidoxyethyltriethoxysilane, 2-glycidoxyethyltrimethoxysilane, 2-glycidoxyethyltriethoxysilane, 1-glycidoxypropyltrimethoxysilane, 1-glycidoxypropyl glycidoxypropyltriethoxysilane, 2-glycidoxypropyltrimethoxysilane, 2-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltripropoxysilane, 3-glycidoxypropyltriisopropoxysilane, 3-glycidoxypropyltributoxysilane, 3-glycidoxypropyltri(methoxyethoxy)silane, 1-glycidoxybutyltrimethoxysilane, 1-glycidoxybutyltriethoxysilane, 2-glycidoxypropyltriethoxysilane Dibutyltrimethoxysilane, 2-glycidoxybutyltriethoxysilane, 3-glycidoxybutyltrimethoxysilane, 3-glycidoxybutyltriethoxysilane, 4-glycidoxybutyltrimethoxysilane, 4-glycidoxybutyltriethoxysilane, (3,4-epoxycyclohexyl)methyltrimethoxysilane, (3,4-epoxycyclohexyl)methyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltripropoxysilane, 2-(3,4-epoxycyclohexyl)ethyltributoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriphenoxysilane, 3-(3,4-epoxycyclohexyl)propyltrimethoxysilane, 3-(3,4-epoxycyclohexyl)propyltriethoxysilane, 4-(3,4-epoxycyclohexyl)butyltrimethoxysilane, 4-(3,4-epoxycyclohexyl)butyltriethoxysilane, trifluoro Methyltrimethoxysilane, trifluoromethyltriethoxysilane, trifluoropropyltrimethoxysilane, trifluoropropyltriethoxysilane, perfluoropropyltrimethoxysilane, perfluoropropyltriethoxysilane, perfluoropentyltrimethoxysilane, perfluoropentyltriethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, tridecafluorooctyltripropoxysilane, tridecafluorooctyltriisopropoxysilane, heptadecafluorodecyltrimethoxysilane, heptadecafluorodecyltriethoxysilane, bis(trifluoromethyl)dimethoxysilane, bis(trifluoropropyl)dimethoxysilane, bis(trifluoropropyl)diethoxysilane, trifluoropropylmethyldimethoxysilane, trifluoropropylmethyldiethoxysilane, trifluoropropylethyldimethoxysilane, trifluoropropylethyldiethoxysilane, heptadecafluorodecylmethyl Examples of the silane include dimethoxysilane, 1-naphthyltrimethoxysilane, 1-naphthyltriethoxysilane, 2-naphthyltrimethoxysilane, 1-anthracenyltrimethoxysilane, 9-anthracenyltrimethoxysilane, 9-phenanthrenyltrimethoxysilane, 9-fluorenyltrimethoxysilane, 2-fluorenyltrimethoxysilane, 2-fluorenonyltrimethoxysilane, 1-pyrenyltrimethoxysilane, 2-indenyltrimethoxysilane, and 5-acenaphthenyltrimethoxysilane. Two or more of these may be used.

[0042] Component (a) can be obtained by hydrolysis and condensation of an organosilane compound, for example, by hydrolyzing an organosilane compound and then subjecting the resulting silanol compound to a condensation reaction in the presence of an organic solvent or without a solvent.

[0043] Various conditions for the hydrolysis reaction can be appropriately set in consideration of the reaction scale, the size and shape of the reaction vessel, etc. For example, it is preferable to add an acid catalyst and water to an organosilane compound in a solvent over 1 to 180 minutes, and then react at room temperature to 110°C for 1 to 180 minutes. By carrying out the hydrolysis reaction under such conditions, a rapid reaction can be suppressed. The reaction temperature is more preferably 30 to 105°C.

[0044] In order to promote the hydrolysis reaction and the dehydration condensation reaction, it is preferable to use a catalyst. Examples of the catalyst include acids such as hydrochloric acid, acetic acid, formic acid, nitric acid, oxalic acid, hydrochloric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, polycarboxylic acids and their anhydrides, bases such as monoethanolamine, diethanolamine, triethanolamine, 3,3-dimethylbutylamine, methylpentylamine, n-butylethylamine, dibutylamine, n-butylamine, pentylamine, isopentylamine, cyclopentylamine, hexylamine, cyclohexylamine, dimethylhexylamine, N,N-dimethylbutylamine, N,N-dimethylhexadecylamine, and N,N-dimethyl-n-octylamine, and pyridine salts of methanesulfonic acid and pyridine salts of ethanesulfonic acid. Organic salts such as silane salt, propanesulfonic acid pyridine salt, benzenesulfonic acid pyridine salt, p-toluenesulfonic acid pyridine salt, xylenesulfonic acid pyridine salt, trifluoromethanesulfonic acid pyridine salt, trifluoroethanesulfonic acid pyridine salt, trifluoropropanesulfonic acid pyridine salt, trifluoroacetic acid pyridine salt, p-toluenesulfonic acid 2,4,6-trimethylpyridine salt, p-toluenesulfonic acid aniline salt, tetramethylammonium p-toluenesulfonate, tetraethylammonium p-toluenesulfonate, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are used. The amount of catalyst added is preferably 0.05 to 5 parts by weight based on 100 parts by weight of the total organosilane compounds used in the hydrolysis reaction. By setting the amount of catalyst within the above range, the hydrolysis reaction can be more efficiently carried out.

[0045] After obtaining a silanol compound by the hydrolysis reaction of the organosilane compound, the reaction liquid is preferably heated as it is at 50° C. or higher and at or lower than the boiling point of the solvent for 1 to 100 hours to carry out a condensation reaction.

[0046] Examples of organic solvents that can be used in the hydrolysis and condensation reaction of organosilane compounds include alcohols such as methanol, ethanol, propanol, isopropanol, butanol, isobutanol, t-butanol, pentanol, 4-methyl-2-pentanol, 3-methyl-2-butanol, 3-methyl-3-methoxy-1-butanol, 1-t-butoxy-2-propanol, and diacetone alcohol; glycols such as ethylene glycol and propylene glycol; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol monoethyl ether. Examples of the solvent include ethers such as dibutyl ether and diethyl ether; ketones such as methyl ethyl ketone, acetylacetone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, diisobutyl ketone, cyclopentanone, and 2-heptanone; amides such as dimethylformamide and dimethylacetamide; acetates such as ethyl acetate, propyl acetate, butyl acetate, isobutyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, methyl lactate, ethyl lactate, and butyl lactate; aromatic or aliphatic hydrocarbons such as toluene, xylene, hexane, and cyclohexane, γ-butyrolactone, N-methyl-2-pyrrolidone, and dimethyl sulfoxide. Two or more of these may be used. From the viewpoints of the transmittance of the cured film and the solubility of each component, diacetone alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether, propylene glycol mono-t-butyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, γ-butyrolactone, and the like are preferred.

[0047] When the hydrolysis reaction produces a compound listed above as an organic solvent or a compound that acts as a solvent, it is also possible to carry out the hydrolysis without a solvent. It is also preferable to adjust the concentration to an appropriate level as a resin composition by adding a solvent after the reaction is completed. In addition, depending on the purpose, after the hydrolysis, an appropriate amount of the produced alcohol, etc. may be distilled and removed under heating or reduced pressure, and then a suitable solvent may be added.

[0048] The amount of the solvent used in the hydrolysis reaction is preferably 50 parts by weight or more and 500 parts by weight or less based on 100 parts by weight of the organosilane compound used as a raw material. By setting the amount of the solvent within the above range, the hydrolysis reaction can be carried out more efficiently.

[0049] The water used in the hydrolysis reaction is preferably ion-exchanged water, and the amount of water is preferably 1.0 to 4.0 moles per mole of silane atoms contained in the organosilane compound.

[0050] The photosensitive resin composition of the present invention contains a metal chelating agent (component (b)). The metal chelating agent refers to a complex compound having a structure in which one or more multidentate ligands are chelated to a metal atom.

[0051] The photosensitive resin composition of the present invention contains component (b), and the formed cured film can improve adhesion to a metal layer containing molybdenum, aluminum, or nickel and chemical resistance while maintaining high transparency, low film stress, and high crack resistance. This is because all or a part of component (b) is incorporated into the film, and component (b) can promote the condensation reaction between unreacted silanol groups remaining in component (a).

[0052] The component (b) is preferably a metal chelating agent represented by the following general formula (3).

[0053] [ka]

[0054] (M represents a metal atom, R 5 are each independently a hydrogen atom, an alkyl group, an aryl group, or an alkenyl group; R 6 and R 7 are each independently a hydrogen atom, an alkyl group, an aryl group, an alkenyl group, or an alkoxy group, j is an integer of 0 to 8, and k is an integer of 1 to 4. Examples of the metal atom M include titanium, zirconium, aluminum, zinc, cobalt, molybdenum, lanthanum, barium, strontium, magnesium, and calcium from the viewpoint of high transparency of the formed cured film. Among these, from the viewpoint of improving adhesion to a metal layer containing molybdenum, aluminum, or nickel while maintaining high transparency, low film stress, and excellent crack resistance, and also from the viewpoint of improving chemical resistance, zirconium or aluminum is preferable as the metal atom M, and zirconium is more preferable. That is, as the (b) component, it is preferable to use an aluminum chelate compound or a zirconium chelate compound, and it is more preferable to use a zirconium chelate compound.

[0055] R of the metal chelating agent represented by the general formula (3) 5 The alkyl, aryl and alkenyl groups in R 6 and R 7 The alkyl group, aryl group, alkenyl group and alkoxy group in the formula (I) may each be substituted with another substituent.

[0056] In the general formula (3), R 5Examples of R include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decanyl, octadecanyl, phenyl, vinyl, allyl, and oleyl. Among these, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-octadecyl, and phenyl are preferred from the viewpoint of the stability of the metal chelating agent. 6 and R 7 Examples of the alkyl group include hydrogen, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, t-butyl, phenyl, vinyl, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, sec-butoxy, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-octadecyl, and benzyloxy. Among these, from the viewpoint of the ease of synthesis and stability of the metal chelating agent, methyl, t-butyl, phenyl, methoxy, ethoxy, and n-octadecyl are preferred.

[0057] Examples of aluminum chelate compounds in which the metal atom M is aluminum include aluminum trisisopropoxide, aluminum tris-n-propoxide, aluminum tris-sec-butoxide, aluminum tris-n-butoxide, aluminum trisphenoxide, aluminum trisacetylacetonate, aluminum tris(2,2,6,6-tetramethyl-3,5-heptanedionate), aluminum trisethylacetoacetate, aluminum trismethylacetoacetate, aluminum trismethylmalonate, aluminum trisethylmalonate, aluminum ethylacetate di(isopropoxide), aluminum acetylacetonate) di(isopropoxide), aluminum methylacetoacetate di(isopropoxide), aluminum octadecylacetoacetate di(isopropylate), and aluminum monoacetylacetonate bis(ethylacetoacetate).

[0058] Examples of zirconium chelate compounds in which the metal atom M is zirconium include zirconium tetra n-propoxide, zirconium tetra n-butoxide, zirconium tetra-sec-butoxide, zirconium tetraphenoxide, zirconium tetraacetylacetonate, zirconium tetra(2,2,6,6-tetramethyl-3,5-heptanedionate), zirconium tetramethylacetoacetate, zirconium tetraethylacetoacetate, zirconium tetramethylmalonate, zirconium tetraethylmalonate, zirconium tetrabenzoylacetonate, zirconium tetradibenzoylmethanate, and zirconium mono n-butoxy. Examples of the acetylacetonate include acetylacetonate bis(ethyl acetoacetate), zirconium mono n-butoxyethyl acetoacetate bis(acetylacetonate), zirconium mono n-butoxy tris(acetylacetonate), zirconium mono n-butoxy tris(acetylacetonate), zirconium di(n-butoxy)bis(ethyl acetoacetate), zirconium di(n-butoxy)bis(acetylacetonate), zirconium di(n-butoxy)bis(ethyl malonate), zirconium di(n-butoxy)bis(benzoylacetonate), zirconium di(n-butoxy)bis(dibenzoylmethanate), and zirconium tetraacetylacetonate.

[0059] Among these, from the viewpoints of improving adhesion to a metal layer containing molybdenum, aluminum or nickel and chemical resistance while maintaining high transparency, low film stress and excellent crack resistance, zirconium tetra-normal propoxide, zirconium tetra-normal butoxide, zirconium tetraphenoxide, zirconium tetraacetylacetonate, zirconium tetraacetylacetonate, aluminum trisacetylacetonate and aluminum tris(2,2,6,6-tetramethyl-3,5-heptanedionate) are preferred, and zirconium tetraacetylacetonate is more preferred.

[0060] The content of component (b) in the photosensitive resin composition of the present invention is, from the viewpoint of improving adhesion and chemical resistance to a metal layer containing molybdenum, aluminum, or nickel, preferably 0.1 wt % or more, and more preferably 0.5 wt % or more, based on 100 wt % of the solid content contained in the photosensitive resin composition; on the other hand, from the viewpoint of maintaining high film transparency and low film stress, the content is preferably 5 wt % or less, and more preferably 3 wt % or less.

[0061] The photosensitive resin composition of the present invention contains a photoradical polymerization initiator (component (c)). The photoradical polymerization initiator refers to a compound that decomposes and / or reacts when irradiated with ultraviolet light having a wavelength of 300 nm to 430 nm, generating radicals. When the photosensitive resin composition contains component (c), the radicals generated from component (c) upon irradiation with ultraviolet light react with the radical polymerizable groups in component (a) described above, or with monofunctional (meth)acrylate compounds and polyfunctional (meth)acrylate compounds described below, thereby imparting photocurability and negative-type photosensitivity.

[0062] Examples of the (c) component include benzoin compounds, benzil ketal compounds, acetophenone compounds, α-aminoalkylphenone compounds, acylphosphine oxide compounds, oxime ester compounds, benzophenone compounds having an amino group, and benzoic acid ester compounds having an amino group. Two or more of these compounds may be used. Among these, from the viewpoint of increasing the curability of the film and maintaining high transparency, it is preferable to use acetophenone compounds, α-aminoalkylphenone compounds, acylphosphine oxide compounds, and oxime ester compounds, and acetophenone compounds and oxime ester compounds are more preferable.

[0063] Examples of acetophenone compounds include 2,2-dimethoxy-2-phenylacetophenone, α-hydroxyacetophenone, 1-hydroxycyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropynoyl)benzyl)phenyl)-2-methylpropan-1-one.

[0064] Examples of α-aminoalkylphenone compounds include 2-methyl-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1.

[0065] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoylphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-(2,4,4-trimethylpentyl)-phosphine oxide.

[0066] Examples of oxime ester compounds include 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1,2-octanedione,1-[4-(phenylthio)-2-(O-benzoyloxime)], 1-phenyl-1,2-butadione-2-(o-methoxycarbonyl)oxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-(O-acetyloxime).

[0067] The amount of component (c) contained in the photosensitive resin composition of the present invention is, from the viewpoint of sufficiently proceeding with radical polymerization and improving the chemical resistance of the cured film, preferably 0.01% by weight or more, and more preferably 0.1% by weight or more, when the solid content of the photosensitive resin composition is 100% by weight, while from the viewpoint of improving the transparency of the cured film, it is preferably 10% by weight or less, and more preferably 8% by weight or less.

[0068] The photosensitive resin composition of the present invention preferably further contains a monofunctional (meth)acrylate (component (d)). The monofunctional (meth)acrylate refers to a compound having one methacryl group or one acrylic group in the molecule. The term "(meth)acrylate" refers to a general term for acrylate (acrylic acid ester) and methacrylate (methacrylic acid ester). In the following, a compound containing a methacryl group may be referred to as a methacrylate, and a compound containing an acrylic group may be referred to as an acrylate. By containing component (d), the methacryl group or acrylic group can react with the radical generated from component (c) by irradiation with ultraviolet light, and the film can be photocured. In addition, by containing component (d), the stress of the formed film can be reduced, the crack resistance can be improved, and the resolution can be improved, compared to the case where a polyfunctional (meth)acrylate described later is used. Here, the meaning of "monofunctional" in monofunctional (meth)acrylate means that one methacryl group or acrylic group is present in the molecule.

[0069] Examples of the component (d) include n-butyl (meth)acrylate, n-hexyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, isostearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and the like. (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-butyloxypropyl (meth)acrylate, 2-hydroxy-3-(2-ethylhexyloxy)propyl (meth)acrylate, dimethylaminoethyl (meth)acrylate Acrylate, diethylaminoethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, N-(meth)acryloyloxyethyl hexahydrophthalimide, trifluoroethyl (meth)acrylate, ethyl carbitol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxytripropylene glycol (meth)acrylate, Examples of such compounds include 2-ethylhexyl EO-modified (meth)acrylate, phenol EO-modified (meth)acrylate, p-nonylphenol EO-modified (meth)acrylate, p-nonylphenol PO-modified (meth)acrylate, o-phenylphenol EO-modified (meth)acrylate, p-cumylphenol EO-modified (meth)acrylate, methoxytriethylene glycol (meth)acrylate, p-phenoxyphenol EO-modified (meth)acrylate, and p-phenoxyphenol PO-modified (meth)acrylate. Two or more of these compounds may be used.

[0070] Among these, from the viewpoint of reducing the stress of the film to be formed and improving the crack resistance, it is preferable to use, as component (d), 2-ethylhexyl EO-modified (meth)acrylate, phenol EO-modified (meth)acrylate, p-nonylphenol EO-modified (meth)acrylate, p-nonylphenol PO-modified (meth)acrylate, o-phenylphenol EO-modified (meth)acrylate, p-cumylphenol EO-modified (meth)acrylate, p-phenoxyphenol EO-modified (meth)acrylate, or p-phenoxyphenol PO-modified (meth)acrylate.

[0071] Furthermore, it is preferable to use a phenol-modified (meth)acrylate as the component (d), and it is more preferable to use a monofunctional (meth)acrylate represented by the following general formula (1) or general formula (2). These may be used in combination. In other words, it is preferable to use either or both of a monofunctional (meth)acrylate represented by the following general formula (1) and a monofunctional (meth)acrylate represented by the following general formula (2) as the component (d).

[0072] [ka]

[0073] (R 1 represents a hydrogen atom or a methyl group, and R 2 represents an alkylene group. X is a substituent bonded to the benzene ring and represents an alkyl group or an aryl group. p is an integer of 0 to 5 and represents the number of substituents (X) bonded to the benzene ring. The benzene ring may have two or more types of X. Furthermore, m represents a positive integer preferably ranging from 2 to 8.

[0074] [ka]

[0075] (R 3 represents a hydrogen atom or a methyl group, and R 4represents an alkylene group, and n represents a positive integer preferably ranging from 2 to 8.

[0076] In the monofunctional (meth)acrylates represented by the above general formula (1) and general formula (2), from the viewpoint of reducing the film stress of the cured film and improving the crack resistance, each of m and n is preferably 2 or more, and more preferably 4 or more.

[0077] The content of the component (d) in the photosensitive resin composition of the present invention is, from the viewpoint of reducing the film stress of the cured film and improving the crack resistance, preferably 3% by weight or more, and more preferably 5% by weight or more, when the solid content of the photosensitive resin composition is taken as 100% by weight. On the other hand, from the viewpoint of improving the chemical resistance of the cured film, the content is preferably 40% by weight or less, and more preferably 35% by weight or less.

[0078] The photosensitive resin composition of the present invention may contain a polyfunctional (meth)acrylate in addition to the component (d). The polyfunctional (meth)acrylate refers to a compound having two or more groups selected from a methacryl group and an acrylic group. By containing the polyfunctional (meth)acrylate, the above-mentioned photocuring can be further promoted, and the crosslinking density of the film can be improved, thereby improving the chemical resistance.

[0079] Examples of the polyfunctional (meth)acrylate include bifunctional (meth)acrylates such as 2,2-[9H-fluorene-9,9-diylbis(1,4-phenylene)bisoxy]diethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dimethyloltricyclodecane di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, glycerin di(meth)acrylate, tripropylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and 1,10-decanediol di(meth)acrylate. Examples of the acrylate include acrylates, acrylic acid esters of tris(2-hydroxyethyl)isocyanuric acid, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, tripentaerythritol octa(meth)acrylate, tetrapentaerythritol nona(meth)acrylate, tetrapentaerythritol deca(meth)acrylate, pentapentaerythritol undeca(meth)acrylate, and pentapentaerythritol dodeca(meth)acrylate. Two or more of these may be used.

[0080] The photosensitive resin composition of the present invention preferably further contains an adhesion improver. The adhesion improver refers to a compound having one or more reactive functional groups in the molecule that improves adhesion to the substrate. By containing the adhesion improver, the adhesion between the coating film and the underlying substrate can be improved. Examples of the adhesion improver include a silane coupling agent having an alkoxysilyl group and / or a silanol group, an alicyclic epoxy compound having an epoxy group, a phosphoric acid ester compound having a phosphoric acid group, and a (meth)acrylamide compound having an amide group. Among these, from the viewpoint of further improving the adhesion between the coating film and the underlying substrate, a silane coupling agent and a (meth)acrylamide compound are preferred.

[0081] The silane coupling agent may be, for example, the organosilane compounds listed as the raw material for the component (a) above. Two or more types of silane coupling agents may be used.

[0082] Among these, from the viewpoint of having a reactive functional group and reacting with other components to improve adhesion and chemical resistance between the coating film and the base substrate, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, vinyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropylmethyldimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 3-mercaptopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 3-isocyanatopropyltriethoxysilane, and p-thrityltrimethoxysilane are preferred.

[0083] Examples of the (meth)acrylamide compound include N-methylacrylamide, N-ethylacrylamide, Nn-propylacrylamide, N-isopropylacrylamide, N-cyclopropylacrylamide, N-hydroxyethylacrylamide, N-methylol acrylamide methyl ether, N-methylol acrylamide ethyl ether, N-methylol acrylamide propyl ether, N-methylol acrylamide butyl ether, N-methoxymethylacrylamide, N-butoxymethylacrylamide, N,N'-methylenebisacrylamide, acryloylmorpholine, diacetone acrylamide, and N Examples of the methacrylamide include N-methylmethacrylamide, N-ethylmethacrylamide, Nn-propylmethacrylamide, N-isopropylmethacrylamide, N-cyclopropylmethacrylamide, N-methoxymethylmethacrylamide, N-butoxymethylmethacrylamide, N,N'-methylenebismethacrylamide, diacetone methacrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methyl,N-ethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, and N-methyl,N-ethylmethacrylamide. Two or more of these may be contained.

[0084] As the adhesion improver, from the viewpoint of improving adhesion to a metal layer containing molybdenum, aluminum, or nickel, it is preferable to use N-methylol acrylamide methyl ether, N-methylol acrylamide ethyl ether, N-methylol acrylamide propyl ether, N-methylol acrylamide butyl ether, N-butoxymethyl acrylamide, N-butoxymethyl methacrylamide, N-methoxymethyl acrylamide, or N-methoxymethyl methacrylamide.

[0085] The photosensitive resin composition of the present invention preferably further contains a polymerization inhibitor. The polymerization inhibitor refers to a compound having a functional group that captures radicals. By containing the polymerization inhibitor, the storage stability and resolution of the photosensitive resin composition can be further improved.

[0086] Examples of the polymerization inhibitor include phenol, catechol, resorcinol, hydroquinone, 4-t-butylcatechol, 2,6-di(t-butyl)-p-cresol, phenothiazine, and 4-methoxyphenol. Examples of commercially available polymerization inhibitors include "IRGANOX" (registered trademark) 1010, 1035, 1076, 1098, 1135, 1330, 1726, 1425, 1520, 245, 259, 3114, 565, and 295 (all trade names, manufactured by BASF Japan Ltd.). Two or more polymerization inhibitors may be used.

[0087] The content of the polymerization inhibitor in the photosensitive resin composition of the present invention is, from the viewpoint of further improving the storage stability and resolution of the photosensitive resin composition and being able to form a pattern with excellent resolution even in a thick film with a thickness of 10 μm or more, preferably 0.01% by weight or more, and more preferably 0.05% by weight or more, when the solid content of the photosensitive resin composition is taken as 100% by weight; on the other hand, from the viewpoint of further improving the chemical resistance of the cured film, the content is preferably 3% by weight or less, and more preferably 1% by weight or less.

[0088] The photosensitive resin composition of the present invention may contain an ultraviolet absorber. By containing an ultraviolet absorber, the weather resistance of the cured film can be further improved. As the ultraviolet absorber, from the viewpoint of transparency and non-coloring, a benzotriazole-based compound, a benzophenone-based compound, or a triazine-based compound is preferable.

[0089] The photosensitive resin composition of the present invention preferably further contains a solvent. The solvent has the function of adjusting the viscosity of the resin composition to a range suitable for coating and improving coating uniformity.

[0090] Examples of the solvent include alcohols such as isopropanol and diacetone alcohol; glycols such as ethylene glycol and propylene glycol; ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and diethylene glycol ethyl methyl ether; methyl ethyl ketone, acetylacetone, methyl propyl ketone, methyl butyl ketone, methyl isobutyl ketone, diisobutyl ketone, and cyclohexane. Examples of suitable ketones include ketones such as cyclopentanone; amides such as dimethylformamide and dimethylacetamide; acetates such as ethyl acetate, propyl acetate, butyl acetate, isobutyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, methyl lactate, ethyl lactate, and butyl lactate; aromatic or aliphatic hydrocarbons such as toluene, xylene, hexane, and cyclohexane, γ-butyrolactone, N-methyl-2-pyrrolidone, and dimethyl sulfoxide. These may be contained in two or more kinds. Among these, from the viewpoint of coating property, diacetone alcohol, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and cyclopentanone are preferred.

[0091] The content of the solvent can be set arbitrarily depending on the application method, etc. For example, when forming a film by spin coating, the content of the solvent is generally set to 30% by weight or more and 90% by weight or less in the photosensitive resin composition.

[0092] The photosensitive resin composition of the present invention preferably contains a surfactant. By containing a surfactant, the coating uniformity of the photosensitive resin composition can be improved. Examples of the surfactant include fluorine-based surfactants, silicone-based surfactants, fluorine-containing thermally decomposable surfactants, polyether-modified siloxane-based surfactants, polyalkylene oxide-based surfactants, poly(meth)acrylate-based surfactants, ammonium lauryl sulfate, polyoxyethylene alkyl ether triethanolamine sulfate, stearylamine acetate, lauryl trimethylammonium chloride, lauryl dimethylamine oxide, lauryl carboxymethyl hydroxyethyl imidazolium betaine, polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, and sorbitan monostearate. Two or more types of surfactants may be used. Among these, silicone-based surfactants and poly(meth)acrylate-based surfactants are preferred from the viewpoint of improving coating uniformity and being excellent in environmental compatibility.

[0093] Examples of commercially available silicone surfactants include "BYK" (registered trademark)-333, BYK-301, BYK-331, BYK-345, and BYK-307 (manufactured by BYK Japan Co., Ltd.). Examples of commercially available poly(meth)acrylate surfactants include "BYK" (registered trademark)-352 (manufactured by BYK Japan Co., Ltd.).

[0094] When it is desired to impart liquid repellency to the film surface, the photosensitive resin composition of the present invention may contain a liquid repellent surfactant as a surfactant. The liquid repellent surfactant refers to a surfactant having one or more reactive functional groups in the molecule and one or more liquid repellent groups in the molecule. As the reactive functional group, a methacryl group or an acrylic group is preferable. As the liquid repellent group, for example, a silicone group, a fluoroalkyl group, or a fluoroalkylene group can be mentioned.

[0095] Next, the cured film of the present invention will be described.

[0096] The cured film of the present invention is obtained by curing the above-mentioned photosensitive resin composition of the present invention. The cured film of the present invention can be suitably used as a sealing layer for a display or a semiconductor, as well as a color filter, a solid-state imaging device, or a fingerprint authentication device, which will be described later.

[0097] The method for producing a cured film using the photosensitive resin composition of the present invention will be described with examples. The method for producing a cured film of the present invention preferably includes a step of curing by light and / or heat without a step of removing all of the (a) component by baking or a stripping solution treatment. Specifically, the photosensitive resin composition of the present invention is applied onto a base substrate, dried to obtain a dry film, and then exposed to light, developed as necessary, and heated (post-baked) to cure the film.

[0098] Examples of the base substrate include glass substrates, metal laminate substrates, silicon wafers, and various films, and can be selected depending on the purpose.

[0099] The coating can be carried out by a coating method such as microgravure coating, spin coating, dip coating, curtain flow coating, roll coating, spray coating, slit die coating, etc., and the coating method can be selected depending on the purpose.

[0100] The drying is preferably performed by evaporating the solvent using a vacuum hot plate and then drying using a heating device. The vacuum hot plate is preferably performed at a temperature of 20 to 80°C and a pressure of 10 to 1000 Pa for 30 to 600 seconds. For example, a hot air oven, a nitrogen oven, a hot plate, etc. can be used as the heating device. The drying temperature by the heating device is preferably 80 to 120°C, and the drying time is preferably 1 to 60 minutes.

[0101] Exposure is a process in which a necessary part of the dry film is photocured by irradiation with light from an exposure device, and an arbitrary part of the dry film is made soluble in a developer. In the exposure process, exposure may be performed through a photomask having a predetermined opening, or an arbitrary pattern may be directly drawn using a laser beam or the like without using a photomask. Also, the entire surface may be exposed without using a photomask.

[0102] Examples of the exposure device include a mask aligner (LA series, manufactured by Nanotec Corporation) and a mirror projection mask aligner (MPA series, manufactured by Canon Inc.). Examples of the actinic rays irradiated in the exposure step include near infrared rays, visible rays, and ultraviolet rays, with ultraviolet rays being preferred. Among ultraviolet rays, it is preferred to use one or more wavelengths selected from 365 nm (i-rays), 405 nm (h-rays), and 436 nm (g-rays). Examples of the light source include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, halogen lamps, and germicidal lamps, with high-pressure mercury lamps and ultra-high-pressure mercury lamps being preferred. The exposure conditions can be appropriately selected depending on the thickness of the dried film to be exposed. In general, 1 to 100 mW / cm 2 Using an ultra-high pressure mercury lamp with an output of 10 to 10,000 mJ / cm 2 It is preferable to perform exposure at an exposure amount of 100 nm (converted into an exposure amount at a wavelength of 365 nm).

[0103] Development is carried out when it is desired to dissolve the unexposed areas and obtain a negative pattern. Examples of the development method include a shower method, a dip method, and a paddle method. The development time is preferably 5 seconds to 10 minutes. Examples of the developer include known alkaline developers, and specific examples include aqueous solutions containing one or more of inorganic alkalis such as hydroxides, carbonates, phosphates, silicates, and borates of alkali metals, amines such as 2-diethylaminoethanol, monoethanolamine, and diethanolamine, and quaternary ammonium salts such as tetramethylammonium hydroxide and choline. After development, it is preferable to rinse with water, and then dry bake at a temperature in the range of 50 to 150°C.

[0104] The post-baking is preferably performed using the above-mentioned heating apparatus. The heating temperature is preferably 85 to 300° C., and the heating time is preferably 10 minutes to 2 hours.

[0105] The cured film of the present invention preferably has a thickness of 10 μm or more and 200 μm or less. The cured film of the present invention preferably has a film stress of 0.01 MPa or more and 10 MPa or less. Since such a cured film has a low film stress, it does not have cracks after post-baking even when a thick film is formed. From the viewpoint of compatibility with the chemical resistance of the cured film, the film stress is more preferably 1 MPa or more. From the viewpoint of suppressing warpage of the substrate after post-baking, the film stress is more preferably 6 MPa or less. The film stress can be measured by the method described in the Examples section.

[0106] From the viewpoint of improving the optical properties of a solid-state imaging element or a fingerprint authentication device described later, the cured film of the present invention preferably has a transmittance at a wavelength of 400 nm per 10 μm of film thickness of 90% or more and 100% or less. The transmittance at a wavelength of 400 nm per 10 μm of film thickness is more preferably 92% or more, and even more preferably 94% or more.

[0107] Next, the color filter, solid-state imaging device, or fingerprint authentication device of the present invention will be described.

[0108] The color filter, solid-state imaging device or fingerprint authentication device of the present invention has the above-mentioned cured film of the present invention.

[0109] Examples of the color filter include color filters using a pigment dispersion type material in which a pigment is dispersed in a photoresist, which is used in flat panel displays such as liquid crystal displays, etc. The color filter of the present invention may have the cured film of the present invention between a substrate and a color filter layer, or on a color filter layer.

[0110] Examples of the solid-state imaging element include a CCD image sensor and a CMOS image sensor, with a CMOS image sensor being more preferred.

[0111] Examples of the fingerprint authentication device include an ultrasonic fingerprint authentication device, an optical fingerprint authentication device, etc. The optical under-display type fingerprint authentication device is more preferable because it has higher authentication accuracy.

[0112] The solid-state imaging element or fingerprint authentication device of the present invention is composed of, for example, a substrate, a sensor, wiring, a light-shielding layer, a transparent medium layer, and a microlens. The transparent medium layer is preferably the cured film of the present invention. The wiring or the light-shielding layer is preferably a metal layer containing any one selected from the group consisting of molybdenum, aluminum, and nickel.

[0113] Therefore, one preferred embodiment of the present invention is a solid-state imaging element or fingerprint authentication device having the cured film of the present invention, wherein the solid-state imaging element or the fingerprint authentication device includes wiring or a light-shielding layer, and the wiring or the light-shielding layer contains any one selected from the group consisting of molybdenum, aluminum, and nickel. EXAMPLES

[0114] The present invention will be described in more detail below with reference to specific examples, but these are merely illustrative and the present invention is not limited to the following examples. Among the compounds used below, those using abbreviations are shown below. PGMEA: Propylene glycol monomethyl ether acetate BHT: Di-t-butyl hydroxytoluene (2,6-di-t-butyl-p-cresol) D-1: Diphenylsilanediol D-2: Methylphenyldimethoxysilane D-3: Cyclohexylmethyldimethoxysilane D-4: Dicyclopentyldimethoxysilane D-5: 3-Methacryloxypropylmethyldimethoxysilane D-6: Dimethyldimethoxysilane D'-1: 3-Methacryloxypropyltrimethoxysilane D'-2: Methyltrimethoxysilane D'-3: 3-trimethoxysilylpropylsuccinic anhydride D'-4: 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane Regarding the evaluation method, if the number of evaluation samples is not stated, the evaluation is performed with one evaluation sample, and if the temperature is not specified for each evaluation and synthesis condition, the evaluation was performed at room temperature.

[0115] The weight average molecular weights of the siloxane resins in Synthesis Examples 1 to 14 and the acrylic resin in Synthesis Example 15 were determined by gel permeation chromatography (GPC) in the following manner, and were calculated as polystyrene equivalent values. Equipment: Waters GPC measurement equipment with RI detector (2695) Column: PLgelMIXED-C column (Polymer Laboratories, 300 mm) x 2 (connected in series) Measurement temperature: 40℃ Flow rate: 1mL / min Solvent: 0.5% by weight solution in tetrahydrofuran (THF) Standard material: polystyrene Detection mode: RI.

[0116] [Synthesis Example 1] Siloxane resin solution (PS-1) A 500 mL three-neck flask was charged with 79.43 g of PGMEA, 34.05 g (0.25 mol) of methyltrimethoxysilane, 34.85 g (0.15 mol) of 3-methacryloxypropylmethyldimethoxysilane, 12.32 g (0.05 mol) of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 26.23 g (0.10 mol) of 3-trimethoxysilylpropylsuccinic anhydride, 97.43 g (0.45 mol) of diphenylsilanediol, and 0.174 g of BHT (0.50 wt% relative to 3-methacryloxypropylmethyldimethoxysilane), and the flask was immersed in a 40°C oil bath and stirred. An aqueous phosphoric acid solution in which 2.05 g of phosphoric acid (1.0 wt% relative to the charged monomer) was dissolved in 28.80 g of water was added as a catalyst using a dropping funnel over 10 minutes. After stirring at 40°C for 1 hour, the oil bath temperature was set to 70°C and stirred for 1 hour, and the oil bath temperature was further increased to 120°C. One hour after the start of the temperature increase, the internal temperature of the solution reached 100°C, and the mixture was heated and stirred for 2 hours (internal temperature: 100 to 110°C). During the reaction, a total of 66 g of by-products, methanol and water, was distilled out. PGMEA was added to the obtained PGMEA solution of siloxane resin so that the concentration of siloxane resin was 65% by weight. 2 parts by weight of a weakly basic ion exchange resin ("Amberlite" (registered trademark) A21, manufactured by Organo Corporation) was added to 100 parts by weight of this solution and stirred at room temperature for 12 hours to remove the phosphoric acid catalyst. Thereafter, the ion exchange resin was removed by filtration, and a siloxane resin solution (PS-1) was obtained. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,500 (polystyrene equivalent).

[0117] [Synthesis Example 2] Siloxane resin solution (PS-2) A siloxane resin solution (PS-2) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 89.06 g, the amount of methyltrimethoxysilane added to 20.43 g (0.15 mol), and the amount of diphenylsilanediol added to 118.97 g (0.55 mol), and an aqueous phosphoric acid solution in which 2.13 g of phosphoric acid (1.0 wt % based on the charged monomer) was dissolved in 23.40 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,300 (polystyrene equivalent).

[0118] [Synthesis Example 3] Siloxane resin solution (PS-3) A siloxane resin solution (PS-3) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 98.69 g, the amount of methyltrimethoxysilane added to 6.81 g (0.05 mol), and the amount of diphenylsilanediol added to 140.60 g (0.65 mol), and an aqueous phosphoric acid solution in which 2.21 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 18.00 g of water was used as the catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,000 (polystyrene equivalent).

[0119] [Synthesis Example 4] Siloxane resin solution (PS-4) A siloxane resin solution (PS-4) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 64.98 g, the amount of methyltrimethoxysilane added to 54.48 g (0.40 mol), and the amount of diphenylsilanediol added to 64.89 g (0.30 mol), and an aqueous phosphoric acid solution in which 1.93 g of phosphoric acid (1.0 wt % based on the charged monomer) was dissolved in 36.90 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,700 (polystyrene equivalent).

[0120] [Synthesis Example 5] Siloxane resin solution (PS-5) A siloxane resin solution (PS-5) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 50.53 g, the amount of methyltrimethoxysilane added to 74.91 g (0.55 mol), and the amount of diphenylsilanediol added to 32.45 g (0.15 mol), and an aqueous phosphoric acid solution in which 1.81 g of phosphoric acid (1.0 wt % based on the charged monomer) was dissolved in 45.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,800 (polystyrene equivalent).

[0121] [Synthesis Example 6] Siloxane resin solution (PS-6) A siloxane resin solution (PS-6) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 55.14 g, 82.03 g (0.45 mol) of methylphenyldimethoxysilane was added instead of diphenylsilanediol, and an aqueous phosphoric acid solution in which 1.90 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 45.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,500 (polystyrene equivalent).

[0122] [Synthesis Example 7] Siloxane resin solution (PS-7) A siloxane resin solution (PS-7) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 56.57 g, 84.74 g (0.45 mol) of cyclohexylmethyldimethoxysilane was added instead of diphenylsilanediol, and an aqueous phosphoric acid solution in which 1.92 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 45.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 3,000 (polystyrene equivalent).

[0123] [Synthesis Example 8] Siloxane resin solution (PS-8) A siloxane resin solution (PS-8) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 66.10 g, 102.78 g (0.45 mol) of dicyclopentyldimethoxysilane was added instead of diphenylsilanediol, and an aqueous phosphoric acid solution in which 2.10 g of phosphoric acid (1.0 wt % based on the charged monomer) was dissolved in 45.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,800 (polystyrene equivalent).

[0124] [Synthesis Example 9] Siloxane resin solution (PS-9) A siloxane resin solution (PS-9) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 40.37 g, 54.09 g (0.45 mol) of dimethyldimethoxysilane was added instead of diphenylsilanediol, and an aqueous phosphoric acid solution in which 1.62 g of phosphoric acid (1.0 wt % based on the charged monomer) was dissolved in 45.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 3,000 (polystyrene equivalent).

[0125] [Synthesis Example 10] Siloxane resin solution (PS-10) A siloxane resin solution (PS-10) was obtained in the same manner as in Synthesis Example 1, except that 3-trimethoxysilylpropylsuccinic anhydride was not added, the amount of PGMEA added at the beginning of the polymerization was changed to 34.85 g, the amount of methyltrimethoxysilane added was changed to 47.67 g (0.35 mol), and an aqueous phosphoric acid solution in which 1.92 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 27.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,000 (polystyrene equivalent).

[0126] [Synthesis Example 11] Siloxane resin solution (PS-11) A siloxane resin solution (PS-11) was obtained in the same manner as in Synthesis Example 1, except that methyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane were not added, the amount of PGMEA added at the beginning of the polymerization was changed to 105.41 g, the amount of diphenylsilanediol added was changed to 162.23 g (0.75 mol), and an aqueous phosphoric acid solution in which 2.23 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 12.60 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 1,200 (polystyrene equivalent).

[0127] [Synthesis Example 12] Siloxane resin solution (PS-12) A siloxane resin solution (PS-12) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 45.71 g, the amount of methyltrimethoxysilane added to 81.72 g (0.60 mol), and the amount of diphenylsilanediol added to 21.63 g (0.10 mol), and an aqueous phosphoric acid solution in which 1.77 g of phosphoric acid (1.0 wt % based on the charged monomer) was dissolved in 47.70 g of water was used as the catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,700 (polystyrene equivalent).

[0128] [Synthesis Example 13] Siloxane resin solution (PS-13) A siloxane resin solution (PS-13) was obtained in the same manner as in Synthesis Example 1, except that diphenylsilanediol and 3-methacryloxypropylmethyldimethoxysilane were not added, the amount of PGMEA added at the beginning of the polymerization was changed to 34.65 g, the amount of methyltrimethoxysilane added was changed to 95.34 g (0.70 mol), 37.26 g (0.15 mol) of 3-methacryloxypropyltrimethoxysilane was newly added, and an aqueous phosphoric acid solution in which 1.71 g of phosphoric acid (1.0 wt % relative to the charged monomer) was dissolved in 55.80 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 5,000 (polystyrene equivalent).

[0129] [Synthesis Example 14] Siloxane resin solution (PS-14) A siloxane resin solution (PS-14) was obtained in the same manner as in Synthesis Example 1, except that 3-methacryloxypropylmethyldimethoxysilane was not added, the amount of PGMEA added at the beginning of the polymerization was changed to 83.55 g, the amount of methyltrimethoxysilane added to 34.05 g (0.25 mol), and the amount of diphenylsilanediol added to 129.79 g (0.60 mol), and an aqueous phosphoric acid solution in which 2.02 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 23.40 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,000 (polystyrene equivalent).

[0130] [Synthesis Example 15] Siloxane resin solution (PS-15) A siloxane resin solution (PS-15) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 80.25 g, the amount of 3-methacryloxypropylmethyldimethoxysilane added to 27.88 g (0.12 mol), and the amount of diphenylsilanediol added to 103.83 g (0.48 mol), and an aqueous phosphoric acid solution in which 2.04 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 27.72 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,300 (polystyrene equivalent).

[0131] [Synthesis Example 16] Siloxane resin solution (PS-16) A siloxane resin solution (PS-16) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 80.80 g, the amount of 3-methacryloxypropylmethyldimethoxysilane added to 23.24 g (0.10 mol), and the amount of diphenylsilanediol added to 108.16 g (0.50 mol), and an aqueous phosphoric acid solution in which 2.04 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 27.00 g of water was used as a catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,300 (polystyrene equivalent).

[0132] [Synthesis Example 17] Siloxane resin solution (PS-17) A siloxane resin solution (PS-17) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 81.63 g, the amount of 3-methacryloxypropylmethyldimethoxysilane added to 16.26 g (0.070 mol), and the amount of diphenylsilanediol added to 114.64 g (0.53 mol), and an aqueous phosphoric acid solution in which 2.04 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 25.92 g of water was used as the catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,200 (polystyrene equivalent).

[0133] [Synthesis Example 18] Siloxane resin solution (PS-18) A siloxane resin solution (PS-18) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 82.18 g, the amount of 3-methacryloxypropylmethyldimethoxysilane added to 11.62 g (0.050 mol), and the amount of diphenylsilanediol added to 118.97 g (0.55 mol), and an aqueous phosphoric acid solution in which 2.03 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 25.20 g of water was used as the catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,200 (polystyrene equivalent).

[0134] [Synthesis Example 19] Siloxane resin solution (PS-19) A siloxane resin solution (PS-19) was obtained in the same manner as in Synthesis Example 1, except that the amount of PGMEA added at the beginning of the polymerization was changed to 82.45 g, the amount of 3-methacryloxypropylmethyldimethoxysilane added to 9.29 g (0.040 mol), and the amount of diphenylsilanediol added to 121.13 g (0.56 mol), and an aqueous phosphoric acid solution in which 2.03 g of phosphoric acid (1.0% by weight based on the charged monomer) was dissolved in 24.84 g of water was used as the catalyst. The weight average molecular weight of the obtained siloxane resin was measured by GPC and found to be 2,100 (polystyrene equivalent).

[0135] The composition information of Synthesis Examples 1 to 19 is shown in Table 1.

[0136] [Table 1]

[0137] [Synthesis Example 20] Acrylic resin solution (PA-1) 3g of 2,2'-azobis(isobutyronitrile) and 50g of PGMEA were charged into a 500ml flask. Then, 30g of methacrylic acid, 35g of benzyl methacrylate, and 35g of tricyclo[5.2.1.02,6]decan-8-yl methacrylate were charged, stirred at room temperature for a while, and the flask was replaced with nitrogen, and then heated and stirred at 70°C for 5 hours. Next, 15g of glycidyl methacrylate, 1g of dimethylbenzylamine, 0.2g of p-methoxyphenol, and 100g of PGMEA were added to the obtained solution, and heated and stirred at 90°C for 4 hours. PGMEA was added to the obtained PGMEA solution of acrylic resin so that the solid concentration was 50% by weight, and an acrylic resin solution (PA-1) was obtained. The weight average molecular weight of the obtained acrylic resin was measured by GPC and found to be 10,000. The acid value of the obtained acrylic resin was 118mgKOH / g.

[0138] [Example 1] Photosensitive resin composition (A-1) Under yellow light, 5.36 g of the siloxane resin solution (PS-1) obtained in Synthesis Example 1 was used as the component (a), 0.050 g of zirconium tetraacetylacetonate (trade name "Orgatix" (registered trademark) ZC-150, manufactured by Matsumoto Fine Chemical Co., Ltd. (hereinafter "ZC-150")) was used as the component (b), 0.10 g of 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)] (trade name "Irgacure" (registered trademark) OXE01, manufactured by BASF Japan Ltd. (hereinafter "OXE-01")) was used as the component (c), 1.00 g of p-nonylphenol EO-modified acrylate (trade name "Aronix" (registered trademark) M-113, manufactured by Toagosei Co., Ltd. (hereinafter "M-113")) was used as the component (d), and 2-(3,4-ethylenediaminetetraacetate) was used as an adhesion improver. 0.10 g of N-methoxymethylacrylamide (trade name KBM-303, manufactured by Shin-Etsu Chemical Co., Ltd. (hereinafter referred to as "KBM-303")), 0.25 g of N-methoxymethylacrylamide, 0.015 g of ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate] ("Irganox" (registered trademark) 1010, manufactured by BASF Japan Ltd. (hereinafter referred to as "IRGANOX1010")) as a polymerization inhibitor, and 0.030 g of a 10 wt % diluted solution (corresponding to a concentration of 300 ppm) of a poly(meth)acrylate surfactant ("BYK" (registered trademark) 352, manufactured by BYK Japan Ltd. (hereinafter referred to as "BYK-352")) as a surfactant in PGMEA were dissolved in 3.10 g of PGMEA and stirred. The mixture obtained was filtered through a 1.0 μm filter to prepare a photosensitive resin composition (A-1) with a solid content concentration of 50% by weight. Since the concentration of BYK-352 was extremely low, it was excluded from the weight fraction in the table. Also, BYK-352 was omitted from the table.

[0139] [Examples 2 to 10] Photosensitive resin compositions (A-2) to (A-10) (a) Photosensitive resin compositions (A-2) to (A-10) were prepared in the same manner as in Example 1, except that the siloxane resin solutions (PS-2) to (PS-10) obtained in Synthesis Examples 2 to 10, respectively, were used as the siloxane resin.

[0140] [Example 11] Photosensitive resin composition (A-11) A photosensitive resin composition (A-11) was prepared in the same manner as in Example 1, except that the amount of the siloxane resin solution (PS-1) added was 5.40 g, the amount of the metal chelating agent ZC-150 added was 0.025 g, and the amount of PGMEA added was 3.08 g.

[0141] [Example 12] Photosensitive resin composition (A-12) A photosensitive resin composition (A-12) was prepared in the same manner as in Example 1, except that the amount of the siloxane resin solution (PS-1) added was 5.431 g, the amount of the metal chelating agent ZC-150 added was 0.0050 g, and the amount of PGMEA added was 3.07 g.

[0142] [Example 13] Photosensitive resin composition (A-13) A photosensitive resin composition (A-13) was prepared in the same manner as in Example 1, except that the amount of the siloxane resin solution (PS-1) added was 5.435 g, the amount of the metal chelating agent ZC-150 added was 0.0020 g, and the amount of PGMEA added was 3.07 g.

[0143] [Example 14] Photosensitive resin composition (A-14) A photosensitive resin composition (A-14) was prepared in the same manner as in Example 1, except that the amount of the siloxane resin solution (PS-1) added was 5.21 g, the amount of the metal chelating agent ZC-150 added was 0.15 g, and the amount of PGMEA added was 3.15 g.

[0144] [Example 15] Photosensitive resin composition (A-15) A photosensitive resin composition (A-15) was prepared in the same manner as in Example 1, except that the amount of the siloxane resin solution (PS-1) added was 5.05 g, the amount of the metal chelating agent ZC-150 added was 0.25 g, and the amount of PGMEA added was 3.21 g.

[0145] [Example 16] Photosensitive resin composition (A-16) A photosensitive resin composition (A-14) was prepared in the same manner as in Example 1, except that the amount of the siloxane resin solution (PS-1) added was 4.97 g, the amount of the metal chelating agent ZC-150 added was 0.30 g, and the amount of PGMEA added was 3.23 g.

[0146] [Example 17] Photosensitive resin composition (A-17) A photosensitive resin composition (A-17) was prepared in the same manner as in Example 1, except that 0.050 g of zirconium monoacetylacetonate (trade name "Orgatics" (registered trademark) ZC-540, manufactured by Matsumoto Fine Chemical Co., Ltd. (hereinafter referred to as "ZC-540")) was added instead of ZC-150 as the component (b).

[0147] [Example 18] Photosensitive resin composition (A-18) A photosensitive resin composition (A-18) was prepared in the same manner as in Example 1, except that 0.050 g of zirconium ethyl acetoacetate (trade name "Orgatics" (registered trademark) ZC-580, manufactured by Matsumoto Fine Chemical Co., Ltd. (hereinafter referred to as "ZC-580")) was added instead of ZC-150 as the component (b).

[0148] [Example 19] Photosensitive resin composition (A-19) A photosensitive resin composition (A-19) was prepared in the same manner as in Example 1, except that 0.050 g of aluminum tris(acetylacetonate) (trade name Aluminum Chelate A(a), manufactured by Kawaken Fine Chemicals Co., Ltd. (hereinafter referred to as "AL-A(a)")) was added instead of ZC-150 as the component (b).

[0149] [Example 20] Photosensitive resin composition (A-20) A photosensitive resin composition (A-20) was prepared in the same manner as in Example 1, except that 0.050 g of aluminum tris(ethylacetoacetate) (ALCH-TR, manufactured by Kawaken Fine Chemicals Co., Ltd. (hereinafter referred to as "ALCH-TR")) was added instead of ZC-150 as the component (b).

[0150] [Example 21] Photosensitive resin composition (A-21) A photosensitive resin composition (A-21) was prepared in the same manner as in Example 1, except that 0.050 g of aluminum alkyl acetoacetate diisopropylate (trade name Aluminum Chelate M, manufactured by Kawaken Fine Chemical Co., Ltd. (hereinafter referred to as "AL-M")) was added instead of ZC-150 as the component (b).

[0151] [Example 22] Photosensitive resin composition (A-22) A photosensitive resin composition (A-22) was prepared in the same manner as in Example 1, except that 0.050 g of bisacetylacetonatozinc (hereinafter, "Zn(acac)2") was added instead of ZC-150 as the component (b).

[0152] [Example 23] Photosensitive resin composition (A-23) A photosensitive resin composition (A-23) was prepared in the same manner as in Example 1, except that 1.00 g of 3-phenoxybenzyl acrylate ("Light Acrylate" (registered trademark) POB-A, manufactured by Kyoeisha Chemical Co., Ltd. (hereinafter referred to as "POB-A")) was added instead of M-113 as the component (d).

[0153] [Example 24] Photosensitive resin composition (A-24) A photosensitive resin composition (A-24) was prepared in the same manner as in Example 1, except that 1.00 g of isobornyl acrylate ("Light Acrylate" (registered trademark) IB-XA, manufactured by Kyoeisha Chemical Co., Ltd. (hereinafter referred to as "IB-XA")) was added instead of M-113 as the component (d).

[0154] [ Reference example 25] Photosensitive resin composition (A-25) A photosensitive resin composition (A-25) was prepared in the same manner as in Example 1, except that 1.00 g of EO adduct diacrylate of bisphenol A ("Light Acrylate" (registered trademark) BP-4EAL, manufactured by Kyoeisha Chemical Co., Ltd. (hereinafter referred to as "BP-4EAL")), which is a bifunctional acrylate, was added instead of M-113, which is the component (d).

[0155] [Example 26] Photosensitive resin composition (A-26) A photosensitive resin composition (A-26) was prepared in the same manner as in Example 1, except that 0.10 g of an acetophenone compound, 2,2-dimethoxy-2-phenylacetophenone (trade name "Omnirad" (registered trademark) 651, manufactured by BASF Japan Ltd. (hereinafter referred to as "Omnirad651")), was added instead of OXE-01 as the component (c).

[0156] [Example 27] Photosensitive resin composition (A-27) A photosensitive resin composition (A-27) was prepared in the same manner as in Example 1, except that 0.10 g of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad" (registered trademark) 819, manufactured by BASF Japan Ltd. (hereinafter referred to as "Omnirad819")), which is an acylphosphine oxide compound, was added instead of OXE-01 as the component (c).

[0157] [Example 28] Photosensitive resin composition (A-28) A photosensitive resin composition (A-28) was prepared in the same manner as in Example 1, except that 0.10 g of an α-aminoalkylphenone compound, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (trade name “Omnirad” (registered trademark) 907, manufactured by BASF Japan Ltd. (hereinafter referred to as “Omnirad907”)), was added instead of OXE-01 as the component (c).

[0158] [Examples 29 to 33] Photosensitive resin compositions (A-29) to (A-33) (a) Photosensitive resin compositions (A-29) to (A-33) were prepared in the same manner as in Example 1, except that the siloxane resin solutions (PS-15) to (PS-19) obtained in Synthesis Examples 15 to 19, respectively, were used as the siloxane resin.

[0159] [Comparative Examples 1 to 4] Photosensitive resin compositions (A-34) to (A-37) Photosensitive resin compositions (A-34) to (A-37) were prepared in the same manner as in Example 1, except that the siloxane resin solutions (PS-11) to (PS-14) obtained in Synthesis Examples 11 to 14 were used instead of the siloxane resin solution (PS-1).

[0160] [Comparative Example 5] Photosensitive resin composition (A-38) A photosensitive resin composition (A-38) was prepared in the same manner as in Example 1, except that 6.97 g of the acrylic resin solution (PA-1) obtained in Synthesis Example 15 was added instead of the siloxane resin solution (PS-1) and the amount of PGMEA added was 1.49 g.

[0161] [Comparative Example 6] Photosensitive resin composition (A-39) A photosensitive resin composition (A-39) was prepared in the same manner as in Example 1, except that component (b) ZC-150 was not added, the amount of siloxane resin solution (PS-1) added was 5.44 g, and the amount of PGMEA added was 3.07 g.

[0162] [Comparative Example 7] Photosensitive resin composition (A-40) A photosensitive resin composition (A-40) was prepared in the same manner as in Example 1, except that the component (c) OXE-01 was not added, the amount of the siloxane resin solution (PS-1) added was 5.51 g, and the amount of PGMEA added was 3.04 g.

[0163] The compositions of Examples 1 to 33 and Comparative Examples 1 to 7 are shown in Table 2, that is, Tables 2-1 to 2-6. Note that BYK-352 is omitted. The amount of resin (wt%) is shown based on the resin solid content.

[0164] [Table 2-1]

[0165] [Table 2-2]

[0166] [Table 2-3]

[0167] [Table 1]

[0168] [Table 2-5]

[0169] [Table 2-6]

[0170] The evaluation methods for each example are shown below.

[0171] <Evaluation method> "Crack resistance" The photosensitive resin composition samples were spin-coated onto a 10 cm square alkali-free glass substrate (glass thickness 0.5 mm) using a spin coater (MS-A150, manufactured by Mikasa Co., Ltd.), and then pre-baked for 2 minutes at 100°C using a hot plate (HHP-230SQ, manufactured by AS ONE Co., Ltd.) to produce pre-baked films with thicknesses of 15 μm, 37 μm, 60 μm, and 115 μm, respectively. The obtained pre-baked films were then exposed to light at an exposure dose of 200 mJ / cm using a mask aligner (LA-610, manufactured by Minaga Electric Manufacturing Co., Ltd.) with an ultra-high pressure mercury lamp (g, h, i lines) as the light source. 2 (i-line equivalent value). After that, using an automatic developing device (Takizawa Sangyo Co., Ltd. AD-1200), shower development was performed with a 2.38 wt% TMAH aqueous solution for 60 seconds, and then rinsed with water for 30 seconds. Finally, using an oven (Espec Corp. DHS-42), curing was performed in air at 230°C for 30 minutes to produce cured films with thicknesses of 10 μm, 30 μm, 50 μm, and 100 μm, respectively.

[0172] The obtained glass substrate having the cured film was visually observed, and the "crack resistance" of the cured film was evaluated according to the following criteria. If even one crack was observed, it was judged that "cracks are present" at that film thickness. AA is the best. If it is B or higher, it can be said that the crack resistance is excellent. AA: No cracks at film thicknesses of 10 μm, 30 μm, 50 μm, and 100 μm. A: No cracks at film thicknesses of 10 μm, 30 μm, and 50 μm. Cracks present at film thickness of 100 μm. B: No cracks at film thicknesses of 10 μm and 30 μm. Cracks present at film thicknesses of 50 μm and 100 μm. C: No cracks at 10 μm thickness. Cracks present at 30 μm, 50 μm, and 100 μm thicknesses. D: Cracks were observed at film thicknesses of 10 μm, 30 μm, 50 μm, and 100 μm.

[0173] "Membrane stress" Using the photosensitive resin composition as a sample, a cured film with a thickness of 10 μm was prepared on a 6-inch (15.24 cm) silicon wafer in the same manner as in the evaluation of "crack resistance". The stress of the cured film obtained on the 6-inch (15.24 cm) silicon wafer was measured at room temperature of 23°C using a thin film stress measuring device (manufactured by Toho Technology Co., Ltd.), and the "film stress" was evaluated according to the following criteria. AAA is the best. B or higher was judged to be acceptable. AAA: membrane stress less than 3 MPa. AA: Membrane stress is 3 MPa or more and less than 5 MPa. A: Membrane stress is 5 MPa or more and less than 10 MPa. B: Membrane stress is 10 MPa or more and less than 15 MPa. C: Membrane stress is 15 MPa or more. D: Cracks exist and measurement is not possible.

[0174] "Transmittance" Using the photosensitive resin composition as a sample, a cured film having a thickness of 10 μm was prepared on a Tempax glass substrate (manufactured by AGC Technoglass Co., Ltd.) in the same manner as in the evaluation of "crack resistance". Using a UV-Visible Near-Infrared Spectrophotometer U-4100 (manufactured by Hitachi High-Tech Science Co., Ltd.), the UV-Visible absorption spectrum of the Tempax glass substrate alone was measured and used as a reference. Next, the light transmittance of the obtained Tempax glass substrate with the cured film was measured in the wavelength range of 300 nm to 800 nm from the side on which the cured film was formed, and the "transmittance" was evaluated according to the transmittance value at a wavelength of 400 nm according to the following criteria. A was the best. B or higher was judged to be acceptable. A: Transmittance of 95% or more and 100% or less. B: Transmittance is 90% or more but less than 95%. C: transmittance less than 90%.

[0175] "resolution" The photosensitive resin composition samples were spin-coated onto 10 cm square alkali-free glass substrates (glass thickness 0.5 mm) using a spin coater (MS-A150, manufactured by Mikasa Co., Ltd.), and then pre-baked for 2 minutes at 100°C using a hot plate (HHP-230SQ, manufactured by AS ONE Co., Ltd.) to produce pre-baked films with a thickness of 15 μm. The pre-baked films thus obtained were then exposed to light using a mask aligner (LA-610, manufactured by Minaga Electric Co., Ltd.) with an ultra-high pressure mercury lamp (g, h, i lines) as the light source, through a mask having line and space patterns with widths of 15, 25, 50 μm, and 100 μm, at a mask gap of 100 μm, and an exposure dose of 100 mJ / cm. 2 (i-line equivalent value) Then, using an automatic developing apparatus (Takizawa Sangyo Co., Ltd. AD-1200), the film was shower-developed with a 2.38 wt % tetramethylammonium hydroxide (TMAH) aqueous solution for 60 seconds, and then rinsed with water for 30 seconds.

[0176] The developed patterns were observed under magnification using a microscope adjusted to 100x magnification, and the narrowest line width among the patterns in which no residue was found in the unexposed areas was taken as the resolution. However, if there was residue in the unexposed areas near the 100μm-wide pattern or if the pattern peeled off, it was rated as ">100μm," and if there was no residue in the 15μm-wide pattern and the pattern processing was possible, it was rated as "≦15μm." A resolution of 25μm or less can be said to be excellent.

[0177] "Adhesion to metal layers" A substrate (hereinafter referred to as a "metal laminated substrate") was prepared by forming molybdenum-nickel alloy / aluminum / molybdenum-nickel alloy (film thickness: 20 nm / 300 nm / 20 nm) on a non-alkali glass substrate (glass thickness 0.5 mm) in this order. A cured film having a film thickness of 10 μm was formed on this metal laminated substrate using a photosensitive resin composition as a sample in the same manner as in the evaluation of "crack resistance". Then, an adhesion test was performed on the cured film formed on the metal laminated substrate. In the adhesion test, 11 parallel straight lines were drawn at 1 mm intervals on the surface of the cured film so as to reach the base material of the metal laminated substrate with a cutter knife, and 100 squares of 1 mm x 1 mm were created. Then, cellophane adhesive tape (width = 18 mm, adhesive strength = 3.7 N / 10 mm) was attached to the cut surface of the cured film, and the attached cellophane adhesive tape was rubbed with an eraser (JIS S6050 compliant product) to adhere to the surface. Next, one end of the cellophane adhesive tape was held, and the tape was peeled off instantly while keeping the tape at a right angle to the plate. The cured film after the tape was peeled off was observed, and the number of squares that remained unpeeled among the 100 squares was visually counted. The "adhesion" to the metal layer was evaluated according to the peeled area of ​​the squares according to the following criteria. A grade of 4B or higher was judged to be acceptable. 5B: Peeling area = 0% 4B: Peeling area = more than 0% and less than 5%. 3B: Peeling area = 5% or more but less than 15%. 2B: Peeling area = 15% or more and less than 35%. 1B: Peeling area = 35% or more but less than 65%. 0B: Peeling area = 65% or more.

[0178] "Chemical resistance" Using the photosensitive resin composition as a sample, a metal laminate substrate having a cured film with a thickness of 10 μm was prepared in the same manner as in the evaluation of "adhesion to metal layer". This was immersed in a resist stripping solution N300 (trade name, manufactured by Nagase ChemteX Corporation) at 50° C. for 5 minutes, then washed with ultrapure water for 1 minute and air-dried. For the metal laminate substrate having the cured film after such treatment, an adhesion test was carried out using cellophane adhesive tape in the same manner as in the evaluation of "adhesion to metal layer". "Chemical resistance" was evaluated according to the peeled area of ​​the grid according to the following criteria. 4B or more was judged to be acceptable. 5B: Peeling area = 0% 4B: Peeling area = more than 0% and less than 5%. 3B: Peeling area = 5% or more but less than 15%. 2B: Peeling area = 15% or more and less than 35%. 1B: Peeling area = 35% or more but less than 65%. 0B: Peeling area = 65% or more.

[0179] "Moisture and heat resistance" A 10 μm thick cured film was prepared on a 10 cm square alkali-free glass substrate (glass thickness 0.5 mm) using the photosensitive resin composition as a sample, in the same manner as in the evaluation of "crack resistance". This was placed in a thermo-hygrostat under conditions of 85°C temperature and 85% humidity for 100 hours. Thereafter, the glass substrate with the cured film removed from the thermo-hygrostat was subjected to an adhesion test using cellophane adhesive tape in the same manner as in the evaluation of "adhesion to metal layer". In addition to the evaluation of the peeled area of ​​the grid, the "moisture and heat resistance" was evaluated according to the following criteria based on the visual observation of the appearance. AA is the most excellent. If the moisture and heat resistance is B or higher, it can be said that the moisture and heat resistance is excellent. AA: The peeled area is 0% and no abnormality is observed in appearance. A: The peeled area is more than 0% but less than 5%, and no abnormalities are observed in appearance. B: The peeled area is 5% or more and less than 15%, and no abnormality is observed in appearance. C: The peeled area is less than 5%, but there is an abnormality in the appearance and the film is cloudy. D: The peeled area is 5% or more and less than 15%, and the appearance is abnormal and the film is cloudy. E: Peeling area is 15% or more.

[0180] The evaluation results of each of the Examples and Comparative Examples are shown in Table 3, that is, Table 3-1 to Table 3-3.

[0181] [Table 3-1]

[0182] [Table 2]

[0183] [Table 3-3] [Industrial Applicability]

[0184] The effect film of the photosensitive resin composition of the present invention can be used for color filters, solid-state imaging devices, fingerprint authentication devices, and the like.

Claims

1. A photosensitive resin composition comprising a siloxane resin having a radical polymerizable group (hereinafter referred to as "component (a)"), a metal chelating agent (hereinafter referred to as "component (b)"), a monofunctional (meth)acrylate (hereinafter referred to as "component (d)"), and a photoradical polymerization initiator, wherein in component (a), (R) 2 SiO 2/2 A photosensitive resin composition comprising an organosilane unit represented by the formula (R is an organic group) (hereinafter, such organosilane unit is referred to as "D unit") in an amount of 30 mol% or more and 85 mol% or less, based on 100 mol% of all organosilane units, and comprising, as component (d), either or both of a monofunctional (meth)acrylate represented by the following general formula (1) and a monofunctional (meth)acrylate represented by the following general formula (2): 【Chemistry 1】 (R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkylene group, X is a substituent bonded to the benzene ring and represents an alkyl group or an aryl group, p is an integer of 0 to 5 and represents the number of substituents (X) bonded to the benzene ring. The benzene ring may have two or more types of X, and m represents a positive integer.) 【Chemistry 2】 (R 3 represents a hydrogen atom or a methyl group, R 4 represents an alkylene group, and n represents a positive integer.)

2. 2. The photosensitive resin composition according to claim 1, wherein the component (b) is either or both of an aluminum chelate compound and a zirconium chelate compound.

3. 2. The photosensitive resin composition according to claim 1, wherein the content of component (b) is from 0.1% by weight to 5% by weight based on 100% by weight of the solid content of the photosensitive resin composition.

4. 2. The photosensitive resin composition according to claim 1, wherein component (a) is used, which contains D units in which R contained in the D units are each independently R containing any functional group selected from the group consisting of a methyl group, a phenyl group, a cyclopentyl group, and a cyclohexyl group (however, the R cannot simultaneously be a methyl group).

5. R contained in the D unit is a phenyl group, 2. The photosensitive resin composition according to claim 1, wherein the content of the D units in the component (a) is from 30 mol % to 65 mol % based on 100 mol % of all organosilane units.

6. 2. The photosensitive resin composition according to claim 1, wherein component (a) contains either or both of a carboxyl group and a dicarboxylic anhydride group.

7. A cured film obtained by curing the photosensitive resin composition according to any one of claims 1 to 6.

8. The cured film according to claim 7 , having a film stress of 0.01 MPa or more and 10 MPa or less.

9. The cured film according to claim 7, having a film thickness of 10 μm or more and 200 μm or less.

10. The cured film according to claim 7, which has a transmittance at a wavelength of 400 nm per 10 μm of film thickness of 90% or more and 100% or less.

11. A color filter comprising the cured film according to claim 7.

12. A solid-state imaging device comprising the cured film according to claim 7 .

13. A fingerprint authentication device comprising the cured film according to claim 7.

14. 13. The solid-state imaging device according to claim 12, wherein the solid-state imaging device includes wiring or a light-shielding layer, and the wiring or the light-shielding layer contains any one selected from the group consisting of molybdenum, aluminum, and nickel.

15. 14. The fingerprint authentication device according to claim 13, wherein the fingerprint authentication device includes a wiring or a light-shielding layer, and the wiring or the light-shielding layer contains any one selected from the group consisting of molybdenum, aluminum, and nickel.

Citation Information

Patent Citations

  • Radiation-curable silicone rubber composition

    JP2013095805A

  • Negative photosensitive resin composition and cured film

    WO2018216570A1

  • Resin composition, light-blocking film, method for producing light-blocking film, and substrate having partitioning wall attached thereto

    WO2020008969A1

  • Resin composition, light-shielding film, and substrate with partitioning wall

    WO2023048016A1

  • Photosensitive resin composition, microlens

    WO2023054226A1